Research methods and statistics an integrated approach - Wilson, Janie H.; Joye, Shauna W. (SAGE, 2017)
"Research Methods and Statistics: An Integrated Approach by Janie H. Wilson and Shauna W. Joye offers a completely integrated approach to teaching research methods and statistics by presenting a research question accompanied by the appropriate methods and statistical procedures needed to address it. Research questions and designs become more complex as chapters progress, building on simpler questions to reinforce student learning. Using a conversational style and research examples from published works, this comprehensive book walks readers through the entire research process and includes ample pedagogical support for SPSS, Excel, and APA style"--Provided by Amazon.